2015
DOI: 10.1063/1.4939391
|View full text |Cite
|
Sign up to set email alerts
|

Increasing computational efficiency of cochlear models using boundary layers

Abstract: Our goal is to develop methods to improve the efficiency of computational models of the cochlea for applications that require the solution accurately only within a basal region of interest, specifically by decreasing the number of spatial sections needed for simulation of the problem with good accuracy. We design algebraic spatial and parametric transformations to computational models of the cochlea. These transformations are applied after the basal region of interest and allow for spatial preservation, driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In this study, we consider a way to increase the efficiency by a different method. It has been reported that errors in the discretization process influence the efficiency [12]. Thus, they focused on rapid variation in the spatial pattern of cochlear responses, and applied a nonuniform grid property to fit the spatial pattern for decreasing the number of discretization errors.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we consider a way to increase the efficiency by a different method. It has been reported that errors in the discretization process influence the efficiency [12]. Thus, they focused on rapid variation in the spatial pattern of cochlear responses, and applied a nonuniform grid property to fit the spatial pattern for decreasing the number of discretization errors.…”
Section: Introductionmentioning
confidence: 99%